Relationship of Measles Immunization with Measles in East Java - Khuril Eka Oktaviasari (Universitas Airlangga, 2018)
ABSTRACTBackground: Measles cases in Indonesia amounted to 12.681 cases in 2016 and East Java Province was the region with the highest number of measles, which amounted to 3765 cases. The coverage of measles immunization in infants has met the target, but the coverage of measles immunization in toddlers has not met the target. Purpose: The aim of this study is to analyze the relationship between measles immunization in infants and toddlers with the number of cases of measles per district/city in East Java Province in 2016. Methods: This study was an observational study with cross sectional study design. The population was all people who suffered from measles per district/city in East Java Province. The sampling method was using the total population. The variables studied were the number of measles immunization in infants and toddlers and the number of cases of measles, while analysis technique used Pearson correlation. Results: This research showed that there was a relationship between infant immunization (p = 0,04) who had weak relationship and no relationship between immunization of toddler (p = 0,92) who had weak relationship with number of measles cases. Conclusion: There was a relationship between measles immunization in infants with number of measles case in East Java Province.